Konsep Kebenaran menurut Pandangan Filsafat Pendidikan Agama Islam dalam Bidang Ontologis, Epistemologis, dan Aksiologis - Halik; Mustham, Zulkifli; Hadisi, La; Wahidin, La Ode (FKDP (Forum Komunikasi Dosen Peneliti), 2025)
The concept of truth in Islamic educational philosophy lies at the heart of forming knowledgeable and virtuous individuals. This article aims to comprehensively explore the meaning of truth in Islamic educational philosophy through three main dimensions: ontological, epistemological, and axiological. Using a qualitative approach through a literature review of classical Muslim thinkers such as Al-Ghazali, Ibn Sina, and Al-Farabi, as well as modern scholars like Syed Naquib Al-Attas and Seyyed Hossein Nasr, this study analyzes the essence, sources, and purposes of truth within Islamic education. The findings reveal that truth originates from Allah SWT as the absolute reality (al-Haqq), is obtained through the integration of revelation, reason, and experience, and carries moral and social significance for human well- being. Therefore, Islamic education regards truth not merely as an object of knowledge but as a means of spiritual and social transformation toward the realization of insan kamil (the perfect human).